Integration of ICT in a smart school in Betong, Sarawak / Dayang Hironi Awang Kipli - Awang Kipli, Dayang Hironi (2013)
The purpose of this study was to identify the teacher's and student’s perception of school ICT readiness. The secondary schools namely national secondary school (Sekolah Menengah Kebangsaan/SMK) was selected for the study. Data were collected using questionnaire and interview techniques. The questionnaire was distributed to a total of 200 randomly selected teacher and student respondents and 165 questionnaires were returned, however only 150 questionnaires were appropriately completed and able to be used for analysis. Data were analysed using descriptive and inferential statistics. The findings revealed that the level of four aspects of readiness including user readiness, management readiness, content readiness and cultural readiness were positively at the highest level. In addition, findings indicated that there was no significant difference in teacher's perception of readiness based on gender. This study indicated that there were significant relationship between the user readiness, management readiness, content readiness and cultural readiness. Besides that, all aspects of readiness positively associated with each other. In terms of the contribution of the significant predictors of ICT integration, the results revealed that there are two important variables namely teacher and student contributed to the variance of ICT readiness. Overall, the findings of this study have implications to the role of principals, teachers and school management in the way to enhance positive integration of ICT readiness. Based on the findings, this study also provides recommendations for improvement of practices and future research.